2005
DOI: 10.1002/mus.20334
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2‐dependent effects of the venom from the new guinean small‐eyed snake Micropechis ikaheka

Abstract: The New Guinean small-eyed snake (Micropechis ikaheka) is a cause of life-threatening envenoming. Previous studies on M. ikaheka venom have indicated the presence of neurotoxins as well as myotoxins. This study examined the in vitro myotoxic effects of M. ikaheka venom and the efficacy of a polyvalent antivenom in neutralizing these effects. Venom (50 microg/ml) produced a slowly developing contracture and inhibition of direct twitches of the chick biventer cervicis nerve-muscle preparation in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The in vitro myotoxic effects of the venom and the efficacy of a polyvalent antivenom in neutralizing these effects were studied. Also, the venom PLA 2 activity was inhibited by alkylation with BPB [125].…”
Section: Other Types Of Pla 2 Inhibitors As Bms-229724 (4-[4-[2-[2-[bmentioning
confidence: 98%
“…The in vitro myotoxic effects of the venom and the efficacy of a polyvalent antivenom in neutralizing these effects were studied. Also, the venom PLA 2 activity was inhibited by alkylation with BPB [125].…”
Section: Other Types Of Pla 2 Inhibitors As Bms-229724 (4-[4-[2-[2-[bmentioning
confidence: 98%
“…Myotoxicity is a critical outcome of systemic toxicity produced by many Australasian elapids, including rarely with death adders (genus Acanthophis ) and taipans (genus Oxyuranus ). It has been suggested that phospholipase A 2 (PLA 2 ) is the major venom component responsible for myotoxicity . Indeed, many snake venoms and isolated PLA 2 toxins display myotoxicity and cytotoxicity (e.g.…”
mentioning
confidence: 99%